The association between a low cerebro-umbilical ratio at 30–34 weeks gestation, increased intrapartum operative intervention and adverse perinatal outcomes. (August 2016) - Twomey, Sarah; Flatley, Christopher; Kumar, Sailesh
Abstract: Introduction: The aim of this study was to investigate the relationship between the cerebro-umbilical ratio (CUR), measured at 30–34 weeks, and adverse intrapartum and perinatal outcomes. Methods: This was a retrospective cross-sectional cohort study of women delivering at the Mater Mothers' Hospital in Brisbane, Australia. Fetal Doppler indices for 1224 singleton pregnancies were correlated with maternal demographics and intrapartum and perinatal outcomes. Only women who attempted vaginal delivery were included in the study. Results: Infants delivered by emergency cesarean section for fetal compromise had the lowest median CUR, 1.65 (IQR 1.17–2.12), compared to any other delivery group. The proportion of infants with a CUR ≤1 who required emergency cesarean section for fetal compromise was 33.3% compared to 9.3% of infants with a CUR >1 (adjusted OR 6.92 (95% CI 2.04–25.75), p < 0.001). However, the detection rate of CUR ≤1 as a predictor for emergency cesarean delivery for fetal compromise was poor (18.9%). Detection rates increased in cohorts of infants born within two weeks of the scan or with birth weights <10th centile or <5th centile. Additionally, a CUR ≤1 was associated with lower median birth weight, higher rates of admission to the neonatal critical care unit and increased neonatal mortality. Discussion: This study suggests that a CUR ≤1, measured at 30–34 weeks, is associated with a greater risk of emergency cesarean delivery for fetal compromise and a number of other adverse perinatal outcomes. The association was strongest in low birth weight babies.